Companding Realizations of the Nonlinear Energy Operator. (20th June 2013) - Demartinos, Andreas-Christos; Kasimis, Chrysostomos; Laoudias, Costas; Psychalinos, Costas
Abstract : Realizations of the nonlinear energy operator (NEO), using the concept of companding filtering, are introduced and compared in this work. For this purpose, the Log-Domain and Sinh-Domain filtering techniques have been followed. Both topologies are constructed from differentiator and multiplier blocks which have been realized through the utilization of nonlinear transconductor cells. Both of the proposed topologies offer the capability of ultra-low voltage operation, thanks to the employment of MOS transistors in the weak inversion. Considering a single power supply voltage of 0.5 V, the behavior of the proposed NEO realizations has been simulated using the Analog Design Environment of the Cadence software and the design kit of the TSMC 130 nm process. Comparison results show that the Sinh-Domain realization offers a more power efficient design than that offered by the Log-Domain realization.